Audiologic profile of patients with ankylosing spondylitis - WANG Yi, SU Jin-mei, WANG Su-ju, LUAN Lan, GAO Zhi-qiang (Jichu yixue yu linchuang, 2021)
Objective To describ the audiologic profile of patients with ankylosing spondylitis. Methods This comparative cross-sectional study on the auditory evaluations was carried out with 24 patients and 25 controls including the pure tone audiometry, tympanometry, distortion product otoacoustic emissions (DPOAE) and auditory brainstem response (ABR) to identify the prevalence, type of hearing loss in diagnosed ankylosing spondylitis patients. Results The prevalence of hearing loss in patient group was 29%, sensorineural hearing loss was 21%, and conductive hearing loss was 8%, which were all significantly higher than that of the control group(P＜0.05). Tympanic pressure curve type“As” was significantly higher than that of control group (P＜0.05). The cochlea was mainly involved in sensorineural hearing loss. Hearing loss affected female more often. Conclusions The prevalence of hearing loss is high, especially in female patients. Hearing loss may be an extra-articular feature of ankylosing spondylitis. Conductive hearing loss may be resulted from the arthritis of the ossicular chain.